Exploring Applications of Artificial Intelligence Tools in Clinical Care and Health Professions Education: An Online Module for Students - Gauri Agarwal; Lokesh Ramamoorthi; Trevor Yuen; Edwin Merced; Jacqueline Brenner; Winfred Wu; Richard Sabina (MedEdPORTAL)
Introduction Health professions schools vary widely in integration of artificial intelligence (AI) into their curriculum, and freely available instructional modules covering AI's applications and implications are lacking. Health professions students need to understand AI's impact on patient care, research, and education. Methods We developed an interactive 30-minute asynchronous, self-paced online module for medical, nursing, and physical therapy students at our institution. The module, built on the Articulate 360 platform for easy dissemination to other schools, comprises videos, tests, and a list of resources for continued learning. It was initially implemented with 200 first-year medical students, who completed pre- and postmodule tests to assess knowledge gain and a feedback survey to assess the module. Results A total of 164 students completed both the pre- and postmodule tests, and 144 completed the feedback survey. The mean percentage of students with correct test responses improved pre- to postmodule from 74% to 87% (p < .001), indicating significant knowledge gain. Feedback comments highlighted the module's relevance, manageable completion time, and video content. Suggestions for improvement included having more interactive elements and providing detailed explanations on complex concepts such as virtual reality and the ethics of AI. Discussion The AI module successfully enhanced knowledge and was well received. Future iterations will incorporate more video content and improved sections on virtual reality and ethics. The module's adaptability and ease of integration make it a valuable resource for other health professions schools and allow students to be informed about the evolving field of AI in health care.